Clinical Evaluation of a New Resilient Denture Liner. Part 1: Compliance and Color Evaluation - Anamaria Villar, BA,1 Igor J. Pesun, DMD, MS,2 Mary E. Brosky, DMD,3 (Journal of Prosthodontics, 2003)
A new experimental resilient denture liner (MPDS-SL; Lai Laboratories, Burnsville, MN) and Molloplast-B (Buffalo Dental Manufacturing, Syosset, NY) were clinically evaluated for compliance and color change over a 1-year period.